The involvement of CD14 in the activation of human monocytes by peptidoglycan monomers - Damir Muhvic; Volker El-Samalouti; Hans-Dieter Flad; Biserka Radoševic-Stašic; Daniel Rukavina (Hindawi Limited, 2001)
Background: Cell-wall components of Gram-positive and Gram-negative bacteria induce the production of cytokines in human peripheral blood mononuclear cells. These cytokines are the main mediators of local or systemic inflammatory reaction that can contribute to the development of innate immunity.